Respuesta :

frika

Consider the function [tex] f(x) = x^2 + 12x. [/tex]

You can rewrite it as

[tex] f(x) = x^2 + 12x=x^2+2\cdot x\cdot 6=x^2+2\cdot x\cdot 6+6^2-6^2=(x+6)^2-36. [/tex]

When x=-6,  

[tex]f(-6)=(-6+6)^2-36=36. [/tex]

The vertex is (-6.-36).

Answer: correct choice is A.

Answer: (–6, –36)

Step-by-step explanation:

We know that to convert a quadratic form [tex]y=ax^2+bx+c[/tex] to vertex form [tex]y=a(x-h)^2+k[/tex] where (h,k) is the vertex , we use the method of completing the square.

Given function=[tex]x^2+12x[/tex]

Which can be written as :

[tex]x^2+12x=x^2+2(x)(6)[/tex], adding and subtracting square of 6, we get

[tex]x^2+2(x)(6)+(6)^2-(6)^2\\=(x+6)^2-6^2\\=(x-(-6))^2-36[/tex]

On comparing with the standard vertex form we get,

Vertex =(–6, –36)